A case study of colouring activities among five special education pupils in Sekolah Kebangsaan Pengkalan Balak, Melaka / Samsinar Othman - Othman, Samsinar (2013)
Visual Art Education is able to develop curiosity in the media and materials exploration. Through the arts, students will interact directly with the environment and learn to expand the capabilities of their skills. The objective of this study is to review the process of colouring among Special Education students. In addition, this study is to find out how the participation of the students during the teaching and learning of Visual Art Education. Learning capabilities of students are also seen whether it is closely related to their artistic skills. Students’ artworks were observed from January to June 2013 to see their progress. Samples involved in this study consisted of 5 Special Education pupils Sekolah Kebangsaan Pengkalan Balak, Melaka. This study used qualitative methods. This method was found to be suitable to understand, explain and explore human values. For information, data collection techniques used is the interview, observation, visual recordings and documentation. Observation was done by looking and interviewing teachers and students during the implementation of the teaching and learning of Visual Art Education. The study found that art activities in the Special Education curriculum helped changed the students in terms of behaviour related to emotional control, social interaction, skills mastery and additional tools and materials science. This indirectly, helped to develop the quality of each Special Education students.